AB0939 Off-label secukinumab dose escalation in the treatment of moderate-to-severe psoriasis: a multicenter, retrospective study. (12th June 2018) - Phung, M.; Ighani, A.; Georgakopoulos, J.R.; Vender, R.; Giroux, L.; Lansang, P.; Yeung, J.
Abstract : Background: There have been significant advancements in the development of biologics over the past decade that revolutionised treatment for psoriasis and psoriatic arthritis. Interleukin (IL)−17A is a pro-inflammatory cytokine that plays a pivotal role in the pathogenesis of psoriatic disease, and is therefore a target for biologic drug development. Secukinumab is an IL-17A antagonist approved in 2015 for the treatment of psoriatic arthritis and moderate-to-severe psoriasis in adults. Its current approved dosing schedule for psoriasis patients is 300 mg subcutaneous weekly for 5 weeks, followed by monthly maintenance dosing. 1 Some psoriasis patients in clinical practice exhibit a suboptimal response to secukinumab or experience relapse with the approved dosing schedule. In these cases, clinicians may use off-label secukinumab dose escalation regimens, which involve increasing the maintenance dosing frequency to every 2 or 3 weeks, or increasing the monthly dose to 450 mg. No guidelines currently exist for high dose secukinumab regimens. Objectives: The objective of this study was to assess the efficacy and safety of off-label high dose secukinumab regimens in adults with moderate-to-severe psoriasis. Methods: We performed a retrospective chart review for adult patients diagnosed with moderate-to-severe psoriasis treated with an off-label secukinumab up-dose regimen. Efficacy was measured using Psoriasis Area and Severity Index (PASI)−75 or a Physician Global Assessment (PGA) score of 0 or 1 after dose escalation. To assess safety, adverse events (AEs) were recorded. Results: Twenty-five patients were included in this study, 13 (52%) of which also had psoriatic arthritis. The mean treatment time with secukinumab prior to dose escalation was 44.5 weeks. Twelve patients had PASI recorded prior to dose escalation, with a mean score of 5.7. Of the remaining 13 patients, 1 had no documentation of disease severity and 12 had PGA scores of 0 (n=2), 1 (n=1), 2 (n=5), 3 (n=2), and 4 (n=2). These patients then increased their dose to 300 mg secukinumab every 3 weeks (n=10), 300 mg every 2 weeks (n=9), or 450 mg monthly (n=6). Mean follow-up time was 15.9 weeks after dose escalation, where 4 patients achieved PASI-75 and 10 achieved PGA 0 or 1. Therefore, 14 out of 25 (56%) patients had effective outcomes from secukinumab dose escalation based on our study endpoints. AEs included one case of the common cold and an upper respiratory tract infection after dose escalation. Conclusions: This study provides evidence of safety and moderate efficacy for high dose secukinumab regimens in psoriasis patients who display an inadequate response to the approved regimen. Increased dosing did not result in more AEs compared to secukinumab phase 3 clinical trials that used the approved regimen. 2 As such, there may be a role for increased dosing in psoriatic arthritis patients. References: [1] Novartis Pharmaceuticals Canada. Dorval, QC. Cosentyx. Available at: https://pdf.hres.ca/dpd_pm/00040683.PDF. Accessed Sept 6, 2017 [2] Langley RG, et al. Secukinumab in Plaque Psoriasis – Results of Two Phase 3 Trials. N Engl J Med. 2014;371:326–338 Disclosure of Interest: None declared